Structures of vortexes near the poles of planets of the solar system - Maslov, V.I.; Cassé, M.; Cheremnykh, O.K.; Fomina, A.P.; Grasso, D.; Kholodov, R.I.; Novak, O.P.; Ovsiannikov, R.T. (Problems of Atomic Science and Technology, 2023)
In the vicinity of the poles of the planets of the solar system, ordered crystals of vortices and intermittency are observed. The formation of vortex structures in the vicinity of the poles of the planets of the solar system is investigated. The conditions for the formation of vortexes are considered. A nonlinear equation was found describing the vortex dynamics and structures were studied. В околицях полюсів планет Сонячної системи спостерігаються впорядковані кристали вихрів і перемежування. Досліджено утворення вихрових структур поблизу полюсів планет Сонячної системи. Розглянуто умови утворення вихорів. Знайдено нелінійне рівняння, що описує динаміку вихорів, досліджено їх структури.